Creativity and Musical Creativity of Primitive Society - Khakimov Nozimjon Nosirovich (Research Parks Publishing LLC, 2021)
the archaeological excavations carried out by the researchers highlighted the history of each period in a unique way and highlighted the social life, lifestyle, culture and spirituality. Theatrical scientist M.Rahmonov, R.I.Gruber, Greek historian Herodotus ' thoughts are cited as substantive information. Information about the chalks found during archaeological excavations is illuminated